Exploring mental toughness and perceived stress of nursing students of Universiti Sains Malaysia - Celina, Tan (2023)
Possessing mental toughness (MT) enables one to bounce back from adversities, feel confident in completing tasks and be assertive in social situations while remaining committed in the face of stress. Stress can serve as a driving force, but too much stress can cause poor performance and stress-related disorders. Nursing students are vulnerable groups with higher risk of burning out, with anxiety and self-efficacy being among the strongest intrinsic predictors of stress. MT has not been explicitly studied in the context of nursing students hence this research was carried out to contribute to the gap in research. This study aimed to explore the suitability of MT in the nursing context and identify stressors pertaining to the current study’s population of interest and pin-pointing visual themes useful for developing exploratory stress-coping neuroimaging paradigm suited for healthcare education context. The current research was broken down and carried out in three phases with nursing students from Universiti Sains Malaysia (USM) exploring: 1) the suitability of the 4/6Cs MT model via reliability testing of MTQ-48 and its correlation with the Nursing Anxiety and Self-Confidence with Clinical Decision Making (NASC-CDM) scale; 2) the visual themes nursing students perceive as stressful by validating images showing scenarios from daily life, academic and clinical situations; lastly, 3) the relationship between Perceived Stress and MT with images/ visual cues perceived as stressful using Perceived Stress Scale (PSS-10) and MTQ-10. Findings from this research show MT have fair to moderate significant correlations with Anxiety (r=-0.293, p<0.001) and Self-Confidence (r=0.429, p<0.001). The initial 48-item MTQ-48 has good reliability with Cronbach’s coefficient alpha of 0.851 but reported unsatisfactory fit across indices after running confirmatory factor analysis (CFA). After refining the items, a modified 10-item Mental Toughness Questionnaire (MTQ-10) presented decent reliability (α=0.789) achieving all recommended minimum values for CFA fit indices. Image validation via Self-Assessment Manikin (SAM) yielded 36 images with low valence and low arousal reflecting stressful emotions when viewing the images. Finally, concurrent stress rating of images with assessment of MT and Perceived Stress reported 31 images have significant correlation with both MT and Perceived Stress, with strong significant negative correlation between total MT scores and Perceived Stress scores (r=-0.768, p<0.001). The goal of this research to explore the suitability of MT in nursing student context and produce relevant visual themes for perceived stress-coping as surrogate of MT for future neuroimaging research is achieved.